Magnetic Resonance Imaging-Visible Perivascular Spaces in the Basal Ganglia Are Associated With the Diabetic Retinopathy Stage and Cognitive Decline in Patients With Type 2 Diabetes - Choi, Eun Young; Park, Yae Won; Lee, Minyoung; Kim, Min; Lee, Christopher Seungkyu; Ahn, Sung Soo; Kim, Jinna; Lee, Seung-Koo (Frontiers in Aging Neuroscience, 2021)
Purpose: To evaluate whether perivascular space (PVS) severity and retinal ganglion cell layer (GCL) thickness differed based on the stage of diabetic retinopathy (DR) and the cognitive status in patients with DR. Methods: A total of 81 DR patients (51 in the nonproliferative group and 30 in the proliferative group) were included in this retrospective, cross-sectional study. PVS severity was assessed in the basal ganglia (BG) and centrum semiovale using magnetic resonance imaging. The total cerebral small vessel disease (SVD) score was determined based on the numbers of lacunes and microbleeds and the severity of white matter hyperintensity. Optical coherence tomography was used to measure foveal and perifoveal GCL thicknesses. Cerebral SVD markers and cognitive function were compared between the groups, and correlations between the BG-PVS severity and the Mini-Mental Status Examination (MMSE) scores and GCL parameters were evaluated. Results: Proliferative DR patients had higher BG-PVS severity (P =.012), higher total cerebral SVD scores (P =.035), and reduced GCL thicknesses in the inferior (P = .027), superior (P = .046), and temporal (P = .038) subfields compared to nonproliferative DR patients. In addition, the BG-PVS severity was negatively correlated with the MMSE score (P = .007), and the GCL thickness was negatively correlated with the BG-PVS severity (P-values < .05 for inferior, superior, and temporal subfields). Conclusions: BG-PVS severity and retinal GCL thickness may represent novel imaging biomarkers reflecting the stage of DR and cognitive decline in diabetic patients. Furthermore, these results suggest a possible link between cerebral and retinal neurodegeneration at the clinical level.